Rol social de las mujeres enterradas en Plataforma Uhle mediante el análisis arquitectónico y ajuar funerario, periodo Mochica III y IV - Lavado Valencia, Sonia Elsa (2022)
The study of the ten funerary contexts (T-16, T-20, T-30, T-52, T-53, T-56, T-58, T-59, T-64 and T-70) of Uhle Platform, has allowed us to define the roles played by the women buried during the Moche III and IV stylistic phase; based on their structure and grave goods, which is evidenced through the quality, quantity and type of offerings with representations of themes and characters linked to religious activity or position of power; and the complexity of the structures where they are found and the symbolism of the architectural spaces of these funerary contexts. This study has allowed us to see that women were not characters in the background as they were previously considered, but that they fulfilled roles and functions equal to those of men.